Genetic Diversity of Acacia Crassicarpa A. Cunn. Ex Benth.Plus Trees of a Provenance Trial in Serdang, Malaysia - Chubo, John Keen (1999)
In the selection of the best species for forest plantation, few criterias have to be considered including morphological and genetic diversity. Thus, the objective of this study was to investigate the diversity of Acacia crassicarpa plus trees using morphological and genetic markers. The genetic structure and mating system of the species were also studied. Plus trees were selected from a provenance trial in Universiti Putra Malaysia (UPM), Serdang based on 8 qualitative and 2 quantitative parameters from 2 regions i.e. Queensland (8 plus trees) and Papua New Guinea (23 plus trees). Leaf samples were collected from these trees and were analysed using 20 isozyme and 15 RAPD markers. The morphological study observed higher variation and better growth perfonnance of trees from Papua New Guinea. However, trees from Queensland have higher retention towards strong wind contradictory to trees from Papua New Guinea. The isozyme analysis observed 36 loci with 24 loci being polymorphic. The mean expected heterozygosities were 0.2316 and 0.2675 for Queensland and Papua New Guinea respectively. The proportions of polymorphic loci for both regions were found to be similar. In the RAPD analysis, a total of 8710ci were scored ranging from 0.10 kb to more than 2.10 kb. Generally, provenances from Papua New Guinea were found to produce higher polymorphism levels as compared to the Queensland provenances. Life history and the ecological characteristics of the species were believed to be the possible reasons for such conditions. Cluster analyses produced three different dendrogram patterns with a tendency of similarity to a certain. The effect of different approaches was suggested to have caused these differences. Relationships of clusters according to number of parent trees, altitudes and longitudes were also observed. The species was found to be highly outcrossing with rates ranging from 0.69 and 0.94. Genetic differentiation in the species observed 60 to 70% of the total diversity to be within provenances. Factors such as reproductive biology, seed dispersal, history and gene flow were suggested to be some of the possible causes for such phenomena.